Prevalence of 25-Hydroxyvitamin D (Vitamin D) Deficiency in a Group of Infertile Women from Baghdad City - Muthana Anad Majid; Wafaa Nasser Hassan; Amna Fadhil Ridha (Biochemistry Research International)
Background. Infertility is a common issue affecting a large number of Iraqi women of reproductive age. The relationship between vitamin D deficiency and infertility has previously drawn the attention of gynecologists, and an increasing number of vitamin D testing has been requested. Methods. 120 women were enrolled in this study between April 2019 and April 2020. Patients were divided into two groups comprising sixty women complaining of infertility, with the other 60 women being fertile and enrolled as controls. All patients were assessed for vitamin D level. Results. In the fertile study group, patients with deficient, insufficient, and sufficient level of vitamin were 28%, 23%, and 48%, respectively (these numbers were rounded to the nearest whole digit, as the numbers for the infertile group were given with that level of precision), whereas the infertile study group showed a statistically significant (p value = 0.002) distribution of vitamin levels with 50%, 35%, and 15% of women being deficient, insufficient, and sufficient, respectively. Conclusions. Vitamin D is significantly deficient in infertile patients which suggests a possible, positive impact if vitamin D is considered in the management of female infertility. Further study with more participants is highly recommended.